Floral diversity expedition in Ladakh: An insight into the exploration, distribution pattern, ethnobotanical, phytochemical studies and conservation strategies - Sabir Hussain; Sheenu Sharma; Ram Chand Bhatti; Anand Narain Singh (Ethnobotany Research and Applications, 2023)
Background: Ladakh, located in the Trans-Himalayan region, is characterized by a sparse distribution of plant and animal life that has adapted to the arid and high-altitude environment. Ladakh’s unique vegetation provides various benefits to the local population, including medicine, phytochemicals, food, fodder, fuelwood, and many other vital services. Over the years, there have been significant developments and changes in the ethnobotanical knowledge in Ladakh. One of the most notable changes is the extensive documentation and research carried out by researchers to systematically record the traditional knowledge held by local communities. The present study aims to report the expedition of wild floral diversity in Ladakh for their exploration, distribution, ecosystem services, ethnobotanical uses, phytochemical extraction, conservation strategies, challenges, and knowledge gaps in research. Methods: To compile the review paper, a comprehensive search was conducted on various web-based platforms, including Web of Science, Scopus, Mendeley, and Google Scholar, to gather relevant literature on the wild vegetation of Ladakh. Different combination of keywords pertaining to floral expedition in Ladakh were used as search string for literature survey on various internet databases. For instance, the search strings used for literature survey on Scopus comprises of keywords such as "Ladakh AND vegetation OR plant," "Phytochemical AND Ladakh," "Ethnobotanical* AND Ladakh," "Ladakh AND Flora AND Diversity," "Plant AND Distribution AND Ladakh," and "Medicinal AND Plants AND Ladakh." Results: Researchers, both from India and abroad, have conducted extensive explorations of the floral diversity in the Ladakh region over the years. They have meticulously documented numerous plant species and conducted in-depth studies covering ethnobotanical significance, phytochemical analysis, distribution patterns, and conservation efforts. Much of this research has been dedicated to understanding the practical benefits of wild plants, including their roles as sources of food, medicine, animal fodder, and fuelwood. The Ladakh region hosts a remarkable diversity of plant species, with more than 150 plant species identified for their medicinal use. Similarly, over 30 species were analyzed for their phytochemical properties and extracted a variety of crucial phytochemicals such as terpenes, alkaloids, phenols, flavonoids, tannins, saponins, and steroids. Plant distribution and diversity in Ladakh are strongly influenced by altitude, with harsh climatic conditions and high altitudes leading to reduced vegetation cover and species richness. Conclusions: Ladakh possesses a unique plant diversity in challenging terrains. Despite topographical and climatic hurdles, researchers from India and abroad have explored its rich flora. Plant distribution shifts with elevation and climate change, peaking at 4000 to 5800 meters and diminishing higher up. The extensive documentation and research conducted by scientists and researchers on the plant’s ethnobotanical significance, has led to the identification of a large number of plant species with medicinal and other significance. Unfortunately, threats to species survival, such as over-collection of underground parts, overgrazing, and exploitation of resources for fuelwood and fodder have been observed, but protective measures and preservation strategies are lacking. Keywords: Floral diversity, Ethnomedicinal, Phytochemicals, Ecosystem services, Conservation, Ladakh